Injuries to World Cup ski and snowboard athletes - Flørenes, T. W.; Nordsletten, L.; Heir, S.; Bahr, R. (Abstractbook. The First International Low Lands Congress on Science and Skiing, Brussels, October 11th, 2008)
Background: We have inadequate knowledge regarding the injury profile of skiers and snowboarders competing at the elite level and limited data to suggest how injuries may be prevented. The FIS Injury Surveillance System was therefore established prior to the winter season 2006-07. Objective: To compare the injury risk and injury pattern between the different FIS disciplines (alpine, freestyle, snowboard, ski jumping, Nordic combined and cross country). Design/setting: Athletes from nine World Cup teams in the six disciplines were interviewed towards the end of the 2006-07 winter season regarding injuries they had sustained during the season. Questions were asked regarding body part, injury type, severity (number of days out of training/competitions), as well as the specific diagnosis. Coaches and/or physical therapists/physicians were interviewed regarding athletes not available. Results: A total of 296 injuries were recorded among 902 athletes, 47% (n=139) in World Cup events (including official training and World Championships) and 28% (n=84) in other training activities on snow. There were a total of 217 (73%) time-loss injuries, where 84 (28%) lead to an absence of >28 days and 76 (26%) with no time loss from training/competition. Alpine, freestyle and snowboard accounted for 84 (28%), 49 (17%) and 100 (34%) of all injuries, respectively. The number of time-loss injures per 100 athletes per season was 28.8 [95% CI: 23.0-36.1] in alpine, 26.8 [19.7-36.5] in freestyle and 44.7 [34.9-57.3] in snowboard, while the Nordic events had 26.3 [15.9-43.6] injuries per 100 athletes per season in Nordic combined, 19.4 [11.3-33.4] in ski jumping and 5.8 [3.2-10.5] for cross country. The knee was the most common injury location with 81 injuries (27%) followed by 36 injuries to the lower back (12%) and 31 head injuries (11%). Conclusion: The injury frequency of elite ski and snowboard athletes is high.